How is the Free Wifi Service Implemented in the Smart City Program in Madiun City? (Open Society Conference, 2023)
The era of the industrial revolution 4.0, strengthening digitalization, especially internet connection services that are affordable to all levels of society, is a necessity. The availability of internet networks that are not evenly distributed and generally can only be enjoyed by the upper middle class encourages the Madiun City Government to create a program called Profit M-Tech, which is the Free Wifi Program for Madiun handheld technology. This study aims as follows: (1) describe the purpose of the free wifi program for Madiun handheld technology; (2) analyze the benefits of the free wifi program for Madiun handheld technology for improving service quality both in the fields of education, economy, socio-culture; and (3) analyze the impact of the free wifi program to support smart city policies and programs in Madiun City. The results of this study show the following conclusions: (1) the Profit M-Tech program in Madiun City has provided a very significant supporting capacity for internet services and access that can be reached by all levels of society, both lower, middle and upper classes; (2) the Profit M-Tech program or free wifi in Madiun City has helped development in several sectors such as online learning, micro, small and medium enterprises (UMKM), IT-based covid handling Education, especially this free wifi program during the covid 19 vandemic was very petrifying; and (3) the Profit M-Tech program or free wifi strongly supports smart city policies and programs in Madiun City.